Optimization of Local Resource Utilization in Rural Economic Potential Development in Tourism and Fisheries Fields - Hartoto; Satria Adhitama; M Yasir Pohan; Nanci Yosepin Simbolon; Alusianto Hamonangan (PT Inovasi Pratama Internasional, 2025)
Paropo Village in Sidikalang District , North Sumatra Province, has great potential in the freshwater fisheries and ecotourism-based tourism sectors. However, the utilization of local resources has not been optimal due to limited knowledge, technology, and market access. This program aims to improve the economic welfare of the community through training and assistance in managing community-based fisheries and tourism. The methods used include needs surveys, environmentally friendly fisheries cultivation training, value-added fish processing, and digital marketing strategies and tourism promotion. The results of the program show an increase in community skills in managing fisheries and tourism businesses, increased income, and the development of community-based business groups. Monitoring and evaluation are carried out periodically to measure the impact and effectiveness of the program. With a systematic and participatory approach , this program is expected to create a sustainable and competitive village economic ecosystem.